Factors Affecting Response Rate and Response Speed in a Mail Survey of Part-Time University Students - Moss, Gwenna M. (Canadian Journal of Higher Education, 1981)
This paper reports the results of an experiment to determine the effects of questionnaire format, reminder format, and followup format on both response rate and response speed in a mail survey. Complete responses were received from 2212 of a sample of 2638 part- time university students, a rate of 83.8%. Mean response time was 16.09 days. Results indicated that: (1) typeset questionnaires were more effective than photocopied question- naires in terms of both response rate and speed; (2) the use of reminder postcards signifi- cantly increased both rate and speed; (3) there was no advantage in hand-addressed reminders over computer-produced labels; and (4) sending a replacement questionnaire as opposed to only a followup letter did not significantly increase response rate, but follow- up format interacted with questionnaire format in influencing response speed.